Peningkatan Senyawa Anti Bacterial Geraniol pada Citronella Oil Sebagai Bahan Baku Pembuatan Perfume Anti-Bacterial - Suryani; Fitria; Nurul F; Syafruddin; Yuhanis Y (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Research is underway to increase the geraniol content of citronella oil by vacuum distillation. Geraniol is a fragrance compound approved by IFRA (International Fragrance Association) and can be used in the formulation of antibacterial perfumes. However, the levels of geraniol in citronella oil are still relatively low. The processing of fragrant citronella oil can be improved by increasing the geraniol content through vacuum distillation. This can be achieved by varying the pressure between 1 and 8 mbar and operating times between 20 and 60 minutes to the final boiling point. The resulting samples were analysed by GC-MS, FT-IR, refractive index and bacterial testing. The results indicate that lower pressure levels can increase geraniol levels. The geraniol content increased by a maximum of 80.11% at a pressure of 1 mbar during the Final Boiling Point operation, with a refractive index of 1.501. FTIR showed an intense broad peak in the range of 2200-3200 cm-1, particularly at 3086.98cm-1, indicating the presence of the OH hydroxyl polymer group in geraniol. The study successfully increased the geraniol content from 20.32% to 80.11%. The results of the antibacterial perfume test showed greater antibacterial activity against Staphylococcus Aerus strains compared to E. coli. The inhibition diameter was 10.13 mm after 48 hours.